Good Corporate Governance, Ukuran Perusahaan, dan Intellectual Capital terhadap Kinerja Keuangan dengan Nilai Perusahaan sebagai Variabel Intervening pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2018-2022 - Novi Putri; Nila Pratiwi; Muhammad Pondrinal (Trending: Jurnal Manajemen dan Ekonomi, 2024)
This research aims to find out how much influence good corporate governance, company size and intellectual capital have on financial performance with company value as an intervening variable in banking companies listed on the indonesia stock exchange for the 2018-2022 period. Documentation methods and types of secondary data. The documentation method used is secondary data analysis. The research results obtained based on the partial test (t test) obtained: good corporate governance partially has a significant effect on company value in banking companies listed on the idx, company size partially has a significant effect on company value in banking companies listed on the idx, intellectual capital partially does not have a significant effect on company value in banking companies listed on the idx, good corporate governance partially has a significant effect on financial performance in banking companies listed on the bei, company size partially has a significant effect on financial performance in banking companies listed on the bei , intellectual capital partially has a significant effect on financial performance in banking companies listed on the idx., company value partially has a significant effect on financial performance in banking companies listed on the bei, good corporate governance partially has no significant effect on Financial Performance with Company Value As an intervening variable in banking companies listed on the IDX, company size partially has a significant effect on financial performance with company value. As an intervening variable in banking companies listed on the BEI, INTELLECTUAL CAPITAL partially has a significant effect on financial performance with company value as an intervening variable. Banking Companies Registered on the IDX.. Finally, the author suggests to the company the need for company management to pay special attention to increasing company value through the variables that have been studied.